2022
DOI: 10.3390/pathogens11030315
|View full text |Cite
|
Sign up to set email alerts
|

First Molecular Evidence for the Presence of Anaplasma phagocytophilum in Naturally Infected Small Ruminants in Tunisia, and Confirmation of Anaplasma ovis Endemicity

Abstract: Anaplasma species are obligate intracellular rickettsial vector-borne pathogens that impose economic constraints on animal breeders and threaten human health. Anaplasma ovis and Anaplasma phagocytophilum infect sheep and goats worldwide. A duplex PCR targeting the msp2 and msp4 genes of A. phagocytophilum and A. ovis, respectively, was developed to analyze the field blood samples collected from sheep and goats. A total of 263 apparently healthy small ruminants from 16 randomly selected flocks situated in 3 bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In a recent investigation from Tunisia, El Hamdi et al [28] have reported that 22.6% of lambs and the entire enrolled ewes (100%) were found infected with A. ovis. In another report from Tunisia, it was reported that prevalence of A. ovis in sheep was 80.4% and the bacterium was detected in 70.3% of enrolled goats [5]. In addition, the prevalence of A. ovis was reported to be 69% in small ruminants of Mongolia [29], 54.5% in China [30], 34.2% in central and Western Kenya [31], 29.7% in Turkey [32], 20.8% in Iran [26], 14.8% in Bangladesh [33] and 1.5% in Thailand [34].…”
Section: Plos Onementioning
confidence: 96%
See 1 more Smart Citation
“…In a recent investigation from Tunisia, El Hamdi et al [28] have reported that 22.6% of lambs and the entire enrolled ewes (100%) were found infected with A. ovis. In another report from Tunisia, it was reported that prevalence of A. ovis in sheep was 80.4% and the bacterium was detected in 70.3% of enrolled goats [5]. In addition, the prevalence of A. ovis was reported to be 69% in small ruminants of Mongolia [29], 54.5% in China [30], 34.2% in central and Western Kenya [31], 29.7% in Turkey [32], 20.8% in Iran [26], 14.8% in Bangladesh [33] and 1.5% in Thailand [34].…”
Section: Plos Onementioning
confidence: 96%
“…[4]. Anaplasma ovis was first identified and reported in 1912 and since then its presence has been frequently reported from Asia, Africa, United States and Europe [5]. The acute phase of A. ovis infection results in fever, severe anemia, weight loss, lower milk production, abortion and jaundice in host animals [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, A. ovis has frequently been detected in ticks of the Rhipicephalus genus [ 10 , 17 , 22 , 26 , 54 , 117 ] and less frequently in Amblyomma ticks [ 26 , 109 ]. Factors that impact the prevalence of A. ovis in small ruminants are suggested to include the sampling technique used, presence of tick vectors, livestock management practices, the climate and ecology of the study area and the immune status and vulnerability of the host animals [ 118 ]. Genetic markers used in the detection and characterization of A. ovis in animals and ticks in Africa include the 16S rRNA, 23S rRNA, msp4 , gltA , msp1a and groEL genes, with a majority of the studies using the msp4 gene [ 9 , 10 , 17 , 54 , 67 , 90 , 94 , 109 , 119 , 120 , 121 , 122 , 123 ] ( Table 1 ).…”
Section: Molecular Epidemiology and Genetic Diversity Of An...mentioning
confidence: 99%
“…Tick-borne pathogens can cause significant losses in livestock reared outdoors in extensive systems, such as sheep [6]. Specifically, for the Mediterranean region, there are several surveys reporting high endemicity of the pathogens of the genus Anaplasma spp.such as A. phagocytophilum, A. ovis, and A. capra-in sheep; however, their pathogenicity is not fully described [2,[7][8][9][10][11][12]. In Greece, sheep farming is particularly important (with a national flock of 8,427,196 animals-Hellenic Statistical Authority, https://www.statistics.…”
Section: Introductionmentioning
confidence: 99%